SIGER SEBAGAI SIMBOL KULTURAL: ANALISIS BENTUK DAN FILOSOFI PADA TRADISI ADAT LAMPUNG - Nafilah Chintia Hariansyah; Siti Nur Azizah (Jurnal Manajemen Pendidikan, 2025)
Culture is a system of ideas, actions, and human creations that are acquired through a learning process and used as guidelines in social life. This study is about the siger as a cultural symbol: an analysis of its form and philosophy in the traditional customs of Lampung. The purpose of this study is to describe the siger as a cultural symbol: an analysis of its form and philosophy in the traditional customs of Lampung. This study uses a descriptive qualitative approach. The results show that Siger Saibatin, with seven curves (sigekh lekuk pitu), symbolizes the seven titles in the Saibatin customary order and reflects the gentle, harmonious character of the community, as well as aesthetic values and family honor. Meanwhile, Siger Pepadun, with nine curves (sigekh lekuk siwo), symbolizes the nine clans in Abung society, showing social hierarchy, unity, and solidarity between clans, while also showing the firm and strong nature of the Pepadun community. Both types of Siger serve as cultural symbols that are not only bridal decorations, but also a means of passing on traditional values, life philosophies, and the social identity of the Lampung community. This study confirms that Siger is an important symbolic medium in preserving Lampung culture amid the currents of modernization and globalization, as well as being a reference for education, cultural documentation, and strategies for preserving Lampung's traditional heritage.